Locally Advanced Thyroglossal Duct Cyst Carcinoma Presenting as a Neck Mass. (9th May 2017) - Tachamo, Niranjan; Le, Brian; Driben, Jeffrey; Magaji, Vasudev
Abstract : Thyroglossal duct cyst carcinoma is rare and occurs in just 1% of cases with thyroglossal duct cysts. It is not always possible to distinguish a thyroglossal cyst harboring malignancy from its benign counterparts unless biopsied, thus posing the dilemma. Currently there is no clear consensus on the optimal management of thyroglossal duct cyst carcinoma. Here we present the case of a 69-year-old female who presented with a midline neck mass and dysphagia and was found to have papillary thyroid cancer in the biopsy specimen of the neck mass. She underwent excision of the mass and the thyroglossal duct cyst along with total thyroidectomy; however, the thyroidectomy specimen showed no malignancy. Her lymph node mapping was negative and she is awaiting radioactive iodine treatment.